ENHANCING SME OPERATIONS THROUGH SYSTEM MANAGEMENT AND RESOURCE TRANSFORMATION (SMART): EVIDENCE FROM PURWAKARTA - Tri Hadi Sulistyanto; Listia Nurazizah; Irawati Irawati; Dedeh Kurniasih; Hanum Nurtaslimah (ULTIMA Management, 2026)
Introduction/Main Objectives: This research aims to understand the experiences of MSMEs in implementing digitalization in the inventory management process and to analyze how operational systems, management, and digitalization interact to improve the efficiency and competitiveness of MSMEs. Background Problems: MSMEs face various challenges in digitalization, including low digital literacy, limited infrastructure and internet access, limited capital and human resources, and the dominance of manual practices in business record-keeping and administration. The adoption rate of digital technology among MSMEs is still low and uneven. Novelty: This research presents novelty by focusing on the actual experiences of MSME actors in inventory management digitalization, using in-depth interviews to gain direct perspectives, which allows for a deeper comprehension of digitalization practices and difficulties in the field. Research Methods: The research used a qualitative approach that utilized in-depth interviews with 8 MSME actors in Purwakarta. The information collected from interviews was cleaned and processed in RIS format, then analyzed and visualized using VOSviewer software to map keywords, inter-concept relationships, and operational thematic patterns. Finding/Results: The VOSviewer analysis identified dominant keywords such as system, business, digital system, recording, process, and manual, which formed five major clusters: system digitalization, products & distribution, recording, operational activities, and manual procedures & traditional administration. The results demonstrate that MSMEs combine manual and digital practices, with a primary focus on workflow, record-keeping, inventory management, business management, and digitalization. Conclusion: Digitalization and system innovation are central themes in MSME operations, while record-keeping, operational processes, and distribution serve as supporting elements. The implementation of specific Management Control Systems can enhance the flexibility, accountability, and ability of MSMEs to face the challenges of digitalization and resource limitations.